Insights from the Absorption Coefficient for the Development of Polarizable (Multipole) Force Fields - Marion Sappl; András Szabadi; Philipp Honegger; Franziska König; Othmar Steinhauser; Christian Schröder (Molecules, 2025)
We present a detailed examination of the absorption coefficients in the THz region for different water models using different types of potentials: the non-polarizable SPC/E, the Drude-polarizable SWM4-NDP and OPC3-pol, IPOL-0.13 and the multipole AMOEBA14 water. The primary focus is on understanding the interplay between permanent and induced dipole moments and their influence on the THz spectrum. Although the induced dipoles strongly contribute to the peak at 200 cm−1, merely increasing the induced dipole moments does not improve the agreement with experiments. We aim to investigate the behavior of the intensity at 200 cm−1 depending on the water model. Furthermore, we dissect the THz spectra of the water models into distinct contributions to gain more insight into the inter- and intramolecular interactions. Intermolecular interactions significantly contribute to the low-frequency peak, while the peak observed at 600 cm−1 can be adequately attributed to intramolecular dipole–dipole interactions.